The potential of ferroptosis combined with radiotherapy in cancer treatment - Lu, Zekun; Xiao, Bingkai; Chen, Weibo; Tang, Tianyu; Zhuo, Qifeng; Chen, Xuemin (Frontiers in Oncology, 2023)
Ferroptosis is a new form of regulatory cell death, that is closely related to the balance of redox reactions and the occurrence and development of cancer. There is increasing evidence that inducing ferroptosis in cells has great potential in the treatment of cancer. Especially when combined with traditional therapy, it can improve the sensitivity of cancer cells to traditional therapy and overcome the drug resistance of cancer cells. This paper reviews the signaling pathways regulating ferroptosis and the great potential of ferroptosis and radiotherapy (RT) in cancer treatment and emphasizes the unique therapeutic effects of ferroptosis combined with RT on cancer cells, such as synergy, sensitization and reversal of drug resistance, providing a new direction for cancer treatment. Finally, the challenges and research directions for this joint strategy are discussed